The Enigmatic Role of Serum & Glucocorticoid Inducible Kinase 1 in the Endometrium - Lang, Florian; Rajaxavier, Janet; Singh, Yogesh; Brucker, Sara Y.; Salker, Madhuri S. (Frontiers in Cell and Developmental Biology, 2020)
The serum- and glucocorticoid-inducible kinase 1 (SGK1) is subject to genetic up-regulation by diverse stimulators including glucocorticoids, mineralocorticoids, dehydration, ischemia, radiation, and hyperosmotic shock. To become active, the expressed kinase protein requires phosphorylation which is accomplished by PI3K/PDK1 and mTOR dependent signalling. SGK1 enhances the expression/activity of various transport proteins including Na+/K+-ATPase as well as ion-, glucose-, and amino acid- carriers in the plasma membrane. SGK1 can further up-regulate diverse ion channels, such as Na+ -, Ca2+-, K+- and Cl- channels. SGK1 regulates expression/activity of a wide variety of transcription factors (such as FKHRL1/Foxo3a, β-catenin, NFκB and p53). SGK1 thus contributes to the regulation of transport, glycolysis, angiogenesis, cell survival, immune regulation, cell migration, tissue fibrosis and tissue calcification. In this review we summarized the current findings that SGK1 plays a crucial function in the regulation of endometrial function. Specifically, it plays a dual role in the regulation of endometrial receptivity necessary for implantation and, subsequently in pregnancy maintenance. Furthermore, fetal programming of blood pressure regulation requires maternal SGK1. Underlying mechanisms are, however, still ill-defined and there is a substantial need for additional information to fully understand the role of SGK1 in the orchestration of embryo implantation, embryo survival and fetal programming.